Damage-control resuscitation increases successful nonoperative management rates and survival after severe blunt liver injury. Issue 2 (February 2015) - Shrestha, Binod; Holcomb, John B.; Camp, Elizabeth A.; Del Junco, Deborah J.; Cotton, Bryan A.; Albarado, Rondel; Gill, Brijesh S.; Kozar, Rosemary A.; Kao, Lillian S.; McNutt, Michelle K.; Moore, Laura J.; Love, Joseph D.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Nonoperative multidisciplinary management for severe (American Association for the Surgery of Trauma Grades IV and V) liver injury has been used for two decades. We have previously shown that Damage Control Resuscitation (DCR) using low-volume, balanced resuscitation improves survival of severely injured trauma patients; however, little attention has been paid to organ-specific outcomes. We wanted to determine if implementation of DCR has improved survival and successful nonoperative management after severe blunt liver injury. METHODS A retrospective study was performed on all adult trauma patients with severe blunt liver injury who were admitted from 2005 to 2011. Patients were divided into pre-DCR (2005–2008) and DCR (2009–2011) groups. Patients who died before leaving the emergency department (ED) were excluded. Outcomes (resuscitation products used, survival, and length of stay) were then compared by univariate and multivariate analyses. RESULTS Between 2005 and 2011, 29, 801 adult trauma patients were admitted, and 1, 412 (4.7%) experienced blunt liver injury. Of these, 244 (17%) sustained Grade IV and V injuries, with 206 patients surviving to leave the ED. The pre-DCR group (2005–2008) was composed of 108 patients, and the DCR group (2009–2011) had 98 patients. The groups were not different in demographics as well as prehospital and ED vital signs or Injury Severity Score (ISS). No change in operative or interventional radiology techniques occurred in this time frame. The DCR cohort had an increase in successful nonoperative management (from 54% to 74%, p < 0.01) as well as a reduction in initial 24-hour packed red blood cell (median, from 13 U to 6.5 U; p < 0.01), plasma (median, from 13 U to 8 U; p < 0.01), and crystalloid (median, from 5, 800 mL to 4, 100 mL; p < 0.01) administration. The DCR treatment was associated with improved survival, from 73% to 94% (p < 0.01). CONCLUSION In patients with severe blunt liver injury, DCR was associated with less crystalloid and blood product use, a higher successful nonoperative management rate, and improved survival. Resuscitation technique may improve outcomes after severe liver injury. LEVEL OF EVIDENCE Therapeutic/care management, level III.